2021
DOI: 10.1007/s12529-021-09999-5
|View full text |Cite|
|
Sign up to set email alerts
|

Pilot Randomized Controlled Trial of Feasibility, Acceptability, and Preliminary Efficacy of a Web-Based Physical Activity and Sedentary Time Intervention for Survivors of Physical Inactivity-Related Cancers

Abstract: Background This pilot study explored the feasibility, acceptability, and usability of a web-based intervention for survivors of physical inactivity-related cancers through a two-arm, 12-week randomized controlled trial. Secondarily, this study tested the change in physical activity (PA) and sedentary time with intervention exposure. Methods Prior to randomization to the intervention ( n = 45) or behavior “as usual” wait-listed control ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Most studies ( n = 16 described in 18 articles) included breast cancer, prostate cancer, and/or colorectal cancer survivors [ 23 , 25 , 26 , 27 , 28 , 29 , 31 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 42 , 43 , 44 ]. Besides these 16 studies, four studies included survivors of breast cancer and other cancer types (gynecologic cancer, testicular cancer, gastrointestinal cancer, lung cancer, osteosarcoma, and other rare cancers) [ 22 , 30 , 40 , 45 ], one included survivors of colorectal cancer and gynecologic cancer [ 32 ], one study included survivors of breast cancer, colorectal cancer, and other cancer types (endometrial cancer, bladder cancer, kidney cancer) [ 21 ], and one study included survivors of leukemia and lymphoma [ 24 ]. The most prevalent type of cancer diagnosis was breast cancer ( n = 1000), followed by prostate cancer ( n = 713) and colorectal cancer ( n = 650).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies ( n = 16 described in 18 articles) included breast cancer, prostate cancer, and/or colorectal cancer survivors [ 23 , 25 , 26 , 27 , 28 , 29 , 31 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 42 , 43 , 44 ]. Besides these 16 studies, four studies included survivors of breast cancer and other cancer types (gynecologic cancer, testicular cancer, gastrointestinal cancer, lung cancer, osteosarcoma, and other rare cancers) [ 22 , 30 , 40 , 45 ], one included survivors of colorectal cancer and gynecologic cancer [ 32 ], one study included survivors of breast cancer, colorectal cancer, and other cancer types (endometrial cancer, bladder cancer, kidney cancer) [ 21 ], and one study included survivors of leukemia and lymphoma [ 24 ]. The most prevalent type of cancer diagnosis was breast cancer ( n = 1000), followed by prostate cancer ( n = 713) and colorectal cancer ( n = 650).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 15 studies [ 22 , 23 , 28 , 29 , 30 , 32 , 35 , 36 , 38 , 39 , 41 , 42 , 43 , 44 , 45 ] that reported information on the education of their participants, more than half (58%) of the participants were college-educated. Among the 10 studies [ 21 , 23 , 28 , 29 , 30 , 38 , 39 , 42 , 43 , 44 ] that reported participants’ work status, 49% of participants worked full- or part-time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations